(untitled) (Annals of Medical Research, 2021)
Aim: Noninflammatory subsynovial connective tissue (SSCT) fibrosis with nerve compression is an obvious feature of carpal tunnel syndrome (CTS). We investigated serum levels of periostin, which is known to have an effect on fibrosis, in patients with CTS. Material and Methods: A total of 39 healthy individuals and 32 patients who were newly diagnosed with CTS were included in this prospective clinical study. Duration of symptoms, severity, unilateral or bilateral side of CTS diagnosis of patients were recorded. Serum samples were received for the measurement of periostin levels from all participants and were analyzed using commercial enzyme-linked immunosorbent assay (ELISA) kits. Results: Serum periostin levels were significantly lower in CTS patients than controls (p=0.030). Additionally, there was no correlation between serum periostin levels and CTS disease regarding the duration of symptoms and electrophysiological severity of symptoms (p > 0.05).Conclusion: In the current study, it was evaluated that there is a significant relation between CTS and serum periostin levels. Periostin may have roles in the pathogenesis of the CTS. This is the first study to determine serum periostin levels in CTS patients.